ANALISIS PERILAKU BULLYING PADA SISWA KELAS V DI SEKOLAH DASAR JAHARUN A - Cindi Safitra Saragih; Yakobus Ndona; Daulat Saragi (Universitas Negeri Medan, 2022)
Bullying is long-term physical and psychological violence perpetrated by a person or group against someone who is unable to defend himself. This study aims to describe Bullying behavior that occurs in fifth grade students at SDN 101964 Jaharun A. This study looks at the types of Bullying that have been carried out by students. The method used is descriptive qualitative with data collection techniques through 3 ways,: observation, interviews and documentation. The results showed that the fifth grade students had been doing Bullying behavior. The behavior is carried out in two types: verbal and physical. Verbally done by mocking parents' names, mocking friends' physical and friend's weaknesses. Meanwhile, physically, it is done by tripping feet, crossing hands and pushing friends.Bullying can be overcome by cooperation school with counseling service, strengthening religious and civic learning.